IT and accounting : the impact of information technology (London ; Melbourne : Chapman and Hall, 1991)
This book is divided into eight parts: Economics; Finance; Financial accounting; Management accounting; Tax and Law; Quantitative methods; Business organization and policy; and Special topics.
Keywords: Accounting; Data processing; Information technology -- Economic aspects; Information storage and retrieval systems -- Accounting; Accounting -- Data processing